Pengaruh Konsumsi Rokok Terhadap Kadar Trigliserida Pada Pria di Banjar Dalem Angantaka - Sugyantari, Pande Putu; Prihatiningsih, Diah; Cahyani, Anak Agung Ayu Eka (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the effect of cigarette consumption on triglyceride levels in men in Banjar Dalem, Angantaka Village as a preventive measure against cardiovascular disease. This comparative observational quantitative study with an experimental design involved 84 male respondents aged 25-45 years who were divided into 42 smokers and 42 non-smokers using purposive sampling. Data collection through interview questionnaires and triglyceride level examination using Sysmex BX-3010 with an enzymatic colorimetric method after a 10-12 hour fast. Data analysis used the Kolmogorov-Smirnov normality test and the Mann-Whitney test for comparison between groups. Based on the above study, the average triglyceride level of the smoker group was 173.19±117.133 mg/dL higher than that of non-smokers 119.62±43.641 mg/dL. The Mann-Whitney test showed a significant difference (p=0.019). The majority of smokers (92.9%) were classified as moderate smokers, with a daily consumption of 11-20 cigarettes and an average duration of 13.36 years. This study concluded that cigarette consumption significantly increases triglyceride levels. These findings have important implications for the development of public health education programs, the implementation of routine lipid profile screening for smokers, and smoking cessation strategies for cardiovascular disease prevention at the community level.